Identifying key barriers to electric vehicle adoption in Bangladesh: Insights from a survey - Hasan, Md Mahmudul; Islam, Ashraful; Islam, Md Nahidul; Ashikujjaman, Md; Hossain, Md Amzad (National Research and Innovation Agency, 2024)
Electric vehicles (EVs) are emerging as a promising solution for reducing greenhouse gas emissions and mitigating environmental damage caused by traditional automobiles. This study examines the barriers to EV adoption in Bangladesh by focusing on various impediments, including technological, infrastructural, financial, behavioral, and external factors. Based on a survey of 111 individuals with substantial knowledge of EVs, this study explores the challenges impeding EV deployment, providing a deeper understanding of the factors that limit their widespread adoption. This research highlights that key obstacles include battery life limitations, inadequate infrastructure, high costs, and long charging durations. By assessing and prioritizing these barriers, the study offers valuable insights for administrators and policymakers to allocate resources effectively and address the most critical issues. The findings underscore the complex, multidimensional nature of EV adoption challenges in Bangladesh and provide actionable recommendations for enhancing decision-making and developing targeted policies to promote the adoption of EVs.